Microdialysis as a tool to determine the local tissue concentration of dicloxacillin in man - Hansen, Kristian Kraft (Br J Clin Pharmacol, 2017)
AIMS: The most common pathogen to cause postoperative infections in Denmark is Staphylococcus aureus. Despite using prophylactic antibiotics, infections are still seen. Whether the tissue concentration is above the minimal inhibitory concentration (MIC) for the pathogen is unknown. Thus, the concentration of dicloxacillin in muscle and adipose tissue was measured after intravenous administration, in healthy men. METHODS: MIC for dicloxacillin against S. aureus was determined using the broth macrodilution method. A microdialysis (MD) catheter was placed in the subcutaneous tissue of the abdomen and in the lateral vastus muscle of the thigh of six healthy male volunteers. They were given 2 g dicloxacillin intravenously. Samples from blood and MD fluid were collected. The unbound dicloxacillin was isolated from plasma. Samples were analysed with high performance liquid chromatography (HPLC). RESULTS: The maximum concentration was reached in muscle tissue after 0.5 h and in adipose tissue after 0.8 h. AUC(0–6h) for the dicloxacillin concentration in adipose tissue was significantly lower when compared to the unbound dicloxacillin concentration in plasma. The dicloxacillin concentration was above the MIC for sensitive S. aureus for a minimum of 2.3 h and a median of 4.1 h in muscle tissue and a minimum of 1.8 h and a median of 3.2 h in adipose tissue. CONCLUSIONS: The unbound dicloxacillin concentration in adipose and muscle tissue remained above the MIC for sensitive S. aureus, for a period sufficient for many orthopaedic procedures. Whether this is true in patients with compromised circulation remains to be investigated.